Effects of monetary policy on the / exchange rate. Is there a 'delayed overshooting puzzle'? - Reinhold Heinlein; Hans-Martin Krolzig (University of Kent, School of Economics, 2011)
The determination of the / exchange rate is studied in a small symmetric macroeconometric model including UK-US differentials in inflation, output gap, short and long-term interest rates for the four decades since the breakdown of Bretton Woods. The key question addressed is the possible presence of a delayed overshooting puzzle in the dynamic reaction of the exchange rate to monetary policy shocks. In contrast to the existing literature, we follow a data-driven modelling approach combining (i) a VAR based cointegration analysis with (ii) a graph-theoretic search for instantaneous causal relations and (iii) an automatic general-to-specific approach for the selection of a congruent parsimonious structural vector equilibrium correction model. We find that the long-run properties of the system are characterized by four cointegration relations and one stochastic trend, which is identified as the long-term interest rate differential and that appears to be driven by long-term inflation expectations as in the Fisher hypothesis. It cointegrates with the inflation differential to a stationary real long-term rate differential and also drives the exchange rate. The short-run dynamics are characterized by a direct link from the short-term to the long-term interest rate differential. Jumps in the exchange rate after short-term interest rate variations are only significant at 10%. Overall, we find strong evidence for delayed overshooting and violations of UIP in response to monetary policy shocks.
Keywords: C22; C32; C50; 330; Exchange Rates; Monetary Policy; Cointegration; Structural VAR; Model Selection